2016
DOI: 10.4236/ajcc.2016.54032
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Clean Development Mechanism in Argentina

Abstract: This paper summarizes the results of the implementation of the CDM in Argentina during the first period of commitment of the Kyoto Protocol. From a total of sixtyfive projects ideas, forty-four achieved registration under the CDM EB while the rest remained approved at national level (12), under evaluation (2), suspended (5) or rejected (2). Most of the projects focused on the generation of electricity from renewable energy, mainly wind energy and the use of landfill gas and methane for energy. Emissions reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Inadequacy in monitoring modalities and verification procedures of co-benefits is also cited as a significant gap in most CDM. Complexities in assessment procedures, design, low awareness, and related bureaucracies have consistently halted the success of the CDM interventions and inclusion of the co-benefits in Brazil (Fernández et al, 2012) and Argentina (Blanco et al, 2016), and Indonesia (Mafira, 2013), calling for improved design protocol to achieve co-benefit goals.…”
Section: Kyoto Protocol and The Clean Development Mechanism Of Kyoto Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequacy in monitoring modalities and verification procedures of co-benefits is also cited as a significant gap in most CDM. Complexities in assessment procedures, design, low awareness, and related bureaucracies have consistently halted the success of the CDM interventions and inclusion of the co-benefits in Brazil (Fernández et al, 2012) and Argentina (Blanco et al, 2016), and Indonesia (Mafira, 2013), calling for improved design protocol to achieve co-benefit goals.…”
Section: Kyoto Protocol and The Clean Development Mechanism Of Kyoto Protocolmentioning
confidence: 99%
“…Additionally, Okubo and Michaelowa (2010) establish the inadequate design of the subsidies related to CDM projects development, noting that the subsidies available are limited to particular aspects, such as institutional capacity building. Blanco et al (2016) indicated that CDM only contributed 45% to technology transfer with limited capacity building support on operation and maintenance in Argentina's case. This has limited the (Disch, 2010), which is the core mandate of CDM.…”
Section: Kyoto Protocol and The Clean Development Mechanism Of Kyoto Protocolmentioning
confidence: 99%